Polymer nano-microsphere composite anion exchange membrane as well as preparation method and application thereof

By introducing polymer nano microspheres and interpenetrating network structures into the anion exchange membrane, the problems of insufficient ion conductivity and durability of the anion exchange membrane in the prior art are solved, and its performance in fuel cells is significantly improved. Have good application prospects.

CN119133544AActive Publication Date: 2024-12-13SICHUAN UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411243716.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-05
Publication Date
2024-12-13
Estimated Expiration
2044-09-05

AI Technical Summary

Technical Problem

The existing anion exchange membrane fuel cells have problems such as low ion conductivity and insufficient long-term durability in high temperature, strong alkali and low humidity environments, which hinder their development in the commercial market.

Method used

The composite structure of polymer nano microspheres and interpenetrating network anion exchange membrane is adopted to prepare the composite anion exchange membrane through specific reaction steps and purification methods to improve its ion conductivity and peak power density.

Benefits of technology

It significantly improves the ion conductivity and peak power density of the composite anion exchange membrane, improves its electrochemical performance and thermal stability in fuel cells, and has good application prospects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119133544A_ABST
    Figure CN119133544A_ABST
Patent Text Reader

Abstract

The invention provides a polymer nano-microsphere composite anion exchange membrane as well as a preparation method and application thereof, and belongs to the technical field of anion exchange membrane fuel cells. According to the invention, polymer nano-microspheres with different particle sizes are prepared by a water dispersion polymerization method, and the polymer nano-microspheres are introduced into a semi-interpenetrating network type anion exchange membrane to prepare the polymer nano-microsphere doped anion exchange membrane. The polymer nano-microsphere composite anion exchange membrane obtained through the strategy has good thermal stability and mechanical property, the electrochemical performance of the anion exchange membrane and the performance of a fuel cell assembled by the anion exchange membrane are improved, and the polymer nano-microsphere composite anion exchange membrane has good application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of anion exchange membrane fuel cells, and in particular relates to a polymer nano-microsphere composite anion exchange membrane and a preparation method and application thereof. Background Art

[0002] Anion exchange membranes (AEMs) are the core components of anion exchange membrane fuel cells (AEMFCs). Their main function is to conduct anions (mainly OH - ) and isolate the fuel from the oxidant. Efficient ion conduction capability is essential to improving the performance of fuel cells. In fuel cell components, AEMs need to have good chemical stability to withstand the effects of alkaline environments and electrochemical reactions, have certain mechanical strength and durability to withstand mechanical stress and wear from long-term operation, and have good thermal stability within a certain temperature range. However, existing AEMs have problems such as low ion conductivity and insufficient long-term durability in high temperature, strong alkaline and low humidity environments, which hinder their development in the commercial market. Therefore, designing anion exchange membranes with high ionic conductivity is essential for the development of anion exchange membrane fuel cells with good battery performance.

[0003] The literature (ACS Applied Materials & Interfaces, 2022, 14(33): 38132-38143) discloses an anion exchange membrane material (S1V1)3Q AEM prepared by cross-linking reaction between branched polyethyleneimine and PS-co-PVBC skeleton. However, the anion exchange membrane material has the following problems: (1) (S1V1)3Q AEM has a low ionic conductivity; (2) the peak power density is low, and its working performance in the battery needs to be further improved. Summary of the invention

[0004] The purpose of the present invention is to provide a polymer nano-microsphere composite anion exchange membrane and a preparation method and use thereof.

[0005] The invention provides a composite anion exchange membrane, which is composed of polymer nano-microspheres and interpenetrating network type anion exchange membrane, wherein the mass ratio of the polymer nano-microspheres to the interpenetrating network type anion exchange membrane is 0.1-10:100.

[0006] Furthermore, the mass ratio of the polymer nanospheres to the interpenetrating network type anion exchange membrane is 0.5 to 6:100.

[0007] Furthermore, the mass ratio of the polymer nanospheres to the interpenetrating network type anion exchange membrane is 1 to 2:100.

[0008] Furthermore, the average particle size of the polymer nanospheres is 100 to 1000 nm, preferably 500 to 830 nm, and more preferably 515.1 to 824.9 nm.

[0009] Furthermore, the polymer nanospheres are obtained by reacting a vinyl-containing halogenated aromatic hydrocarbon monomer, an initiator and a dispersant; the mass volume ratio of the vinyl-containing halogenated aromatic hydrocarbon monomer, the initiator and the dispersant is 10mL: 0.1-0.2g: 0.6-1g.

[0010] Furthermore, the vinyl-containing halogenated aromatic hydrocarbon monomer is 4-vinylbenzyl chloride; the initiator is an azo initiator, preferably azobisisobutyronitrile; the dispersant is polyvinylpyrrolidone; the mass volume ratio of the vinyl-containing halogenated aromatic hydrocarbon monomer, the initiator and the dispersant is 10mL:0.11g:0.8g.

[0011] Furthermore, the reaction is carried out under a nitrogen atmosphere; the solvent of the reaction is a mixture of an inorganic solvent and an organic solvent; the temperature of the reaction is 60 to 80° C., and the reaction time is 4 to 16 hours.

[0012] Furthermore, the solvent of the reaction is a mixture of anhydrous ethanol and deionized water in a volume ratio of 15:4; the temperature of the reaction is 70° C., and the reaction time is 6 to 12 hours.

[0013] Furthermore, after the reaction is completed, the following purification step is also included: the reaction solution is centrifuged, the solid is washed with deionized water saturated with nitrogen atmosphere, and vacuum dried at 60° C. for 6 hours to obtain polymer nanospheres.

[0014] Furthermore, the interpenetrating network anion exchange membrane is prepared according to the following steps:

[0015] (i) reacting a vinyl-containing aromatic hydrocarbon monomer, a vinyl-containing halogenated aromatic hydrocarbon monomer and an initiator to obtain a copolymer;

[0016] (ii) reacting the copolymer with a quaternizing agent to obtain a quaternized copolymer;

[0017] (iii) reacting the quaternized copolymer with a crosslinking agent to obtain an interpenetrating network type anion exchange membrane.

[0018] Further, in step (i), the vinyl-containing aromatic hydrocarbon monomer is styrene, the vinyl-containing halogenated aromatic hydrocarbon monomer is 4-vinylbenzyl chloride; the initiator is an azo initiator, preferably azobisisobutyronitrile; the molar ratio of the vinyl-containing aromatic hydrocarbon monomer to the vinyl-containing halogenated aromatic hydrocarbon monomer is 1:0.5-1.5; the mass percentage of the initiator is 0.5-1.5wt%; the reaction is carried out under a nitrogen atmosphere; the reaction temperature is 70-90°C and the reaction time is 20-30 hours;

[0019] In step (ii), the reaction is carried out under a nitrogen atmosphere; the quaternizing agent is trimethylamine; the molar ratio of the vinyl-containing halogenated aromatic hydrocarbon monomer to the quaternizing agent in the copolymer is 1:0.1-1; the solvent of the reaction is an organic solvent; the reaction temperature is 70-90° C. and the reaction time is 4-6 hours;

[0020] In step (iii), the cross-linking agent is branched polyethyleneimine; the mass ratio of the quaternized copolymer to the cross-linking agent is 2 to 4:1; the reaction temperature is 10 to 40° C., and the reaction time is 1 to 3 hours.

[0021] Furthermore, in step (i), the molar ratio of the vinyl-containing aromatic hydrocarbon monomer to the vinyl-containing halogenated aromatic hydrocarbon monomer is 1:1; the mass percentage of the initiator is 1wt%; the reaction temperature is 80°C and the reaction time is 24 hours;

[0022] In step (ii), the molar ratio of the vinyl-containing halogenated aromatic hydrocarbon monomer to the quaternizing agent in the copolymer is 1:0.5; the solvent of the reaction is dimethyl sulfoxide; the reaction temperature is 80° C. and the reaction time is 5 hours;

[0023] In step (iii), the mass ratio of the quaternized copolymer to the cross-linking agent is 3:1; the reaction temperature is 20-30° C., and the reaction time is 2 hours.

[0024] Furthermore, after the reaction in step (i) is completed, the following purification step is further included: dissolving the reactant in toluene, precipitating with anhydrous ethanol, repeating the operation three times, and vacuum drying at 60° C. for 6 h to obtain a copolymer;

[0025] After the reaction in step (ii) is completed, the following purification step is further included: vacuum drying at 60° C. for 12 h, washing with anhydrous ethanol, and vacuum drying at 40° C. for 12 h to obtain a quaternized copolymer.

[0026] The present invention also provides a method for preparing the composite anion exchange membrane, which comprises the following steps: reacting the polymer nano-microspheres with the interpenetrating network type anion exchange membrane, vacuum degassing, and drying to obtain the composite anion exchange membrane.

[0027] Furthermore, the reaction temperature is 10-40° C. and the reaction time is 0.5-1.5 hours.

[0028] Furthermore, the reaction temperature is 20-30° C. and the reaction time is 1 hour.

[0029] Furthermore, after the reaction is completed, the following purification step is also included: soaking the reactants in 1-bromopropane, reacting in vacuum at 20-30°C for 36 hours, drying, soaking in N2-saturated 1M NaOH solution at 20-30°C for 48 hours, and washing with N2-saturated deionized water to obtain a composite anion exchange membrane.

[0030] The present invention also provides the use of the composite anion exchange membrane in preparing a fuel cell.

[0031] The anion exchange membrane material (S1V1) 3Q AEM reported in the literature (ACS Applied Materials & Interfaces, 2022, 14 (33): 38132-38143) is the sample SV AEM of comparative example 1 of the present invention. Compared with (S1V1) 3Q AEM, the present invention achieves the following beneficial effects:

[0032] (1) The ion conductivity of the composite anion exchange membrane of the present invention is better. (S1V1) 3Q AEM has only 106 mS cm at 80 °C. -1 The hydroxide conductivity of the composite anion exchange membrane of the present invention is 2% and 1% respectively, and the prepared SVSPM2 and SVBPM1AEMs have significantly improved ion conductivity (the conductivity at 80°C is 112.8 mS cm -1 and 110.5mS cm -1 ), which were increased by 9.20% and 6.97% respectively compared with the (S1V1)3Q AEM without nanospheres;

[0033] (2) It is well known to those skilled in the art that the peak power density of an anion exchange membrane is one of the important indicators for measuring its performance in a fuel cell. The improvement of the peak power density means that the anion exchange membrane can achieve a higher energy conversion efficiency per unit area, which is of great significance for the performance optimization and practical application of fuel cells. The composite anion exchange membrane of the present invention has a higher peak power density and better working performance in the battery. (S1V1) 3Q AEM at a current density of 270.80 mA cm-2 When the peak power density is 150.33 mW cm -2 The composite anion exchange membrane SVBPM1AEM of the present invention has a current density of 301.26 mA cm -2 When the peak power density is 158.61mW cm -2 ; SVSPM2AEM at a current density of 375.13 mA cm -2 When the peak power density is 168.72mW cm -2 The peak power densities of SVBPM1AEM and SVSPM2AEM were increased by about 5.51% and 12.23% respectively compared with that of (S1V1)3Q AEM without nanospheres.

[0034] Experimental results show that the polymer nanosphere composite anion exchange membrane obtained by the present invention has good thermal stability and mechanical properties, improves the electrochemical properties of the anion exchange membrane and the performance of the fuel cell assembled with the anion exchange membrane, and has good application prospects.

[0035] Obviously, according to the above contents of the present invention, in accordance with common technical knowledge and customary means in the art, without departing from the above basic technical ideas of the present invention, other various forms of modification, replacement or change may be made.

[0036] The above contents of the present invention are further described in detail below through specific implementation methods in the form of examples. However, this should not be understood as the scope of the above subject matter of the present invention being limited to the following examples. All technologies realized based on the above contents of the present invention belong to the scope of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 Schematic diagram of the preparation of PVBC nanospheres and AEMs doped with nanospheres.

[0038] Figure 2 (a, b) XPS total spectra of SPM and BPM and (c, d) particle size diagrams of SPM and BPM.

[0039] Figure 3 (a, b) SEM images of SPM and BPM and (c, d) EDS images of the distribution of C and Cl elements in BPM.

[0040] Figure 4 This is the TGA-DTG curve of SPM.

[0041] Figure 5 Infrared spectra of SV, SVSPM1 and SVBPM1AEMs.

[0042] Figure 6(ac) Surface SEM images of SV, SVSPM1 and SVSPM6AEMs; (d) cross-sectional SEM image of SVSPM6AEM; (e, f) surface SEM images of SVBPM1 and SVBPM6AEMs; (g) EDS image of N element distribution in the cross section of SVSPM6AEM; (h) EDS image of N element distribution on the surface of SVBPM1AEM; (i) actual image of SVSPM1.

[0043] Figure 7 TEM images of SV (a), SVSPM1 (c), SVSPM6 (d), SVBPM1 (g) and SVBPM6 (h) AEMs; 2D AFM phase images of SV (b), SVSPM1 (e), SVSPM6 (f), SVBPM1 (i) and SVBPM6 (j) AEMs.

[0044] Figure 8 (a, b) TGA-DTG curves of SV, SVSPM1, SVSPM6, SVBPM1 and SVBPM6 AEMs; (c, d) mechanical properties test diagrams of SV, SVSPMx and SVBPMy AEMs.

[0045] Fig. 9 Water absorption rate of SVSPMx (a) and SVBPMy (c) AEMs at different temperatures; Swelling degree test diagram of SVSPMx (b) and SVBPMy (d) AEMs at different temperatures.

[0046] Fig.10 (a, b) Ionic conductivity diagrams of SV, SVSPMx and SVBPMy AEMs.

[0047] Fig.11 H2 / O2 fuel cell performance test diagram of AEMFCs prepared from SV, SVBPM1 and SVSPM2AEMs at 60℃. DETAILED DESCRIPTION

[0048] The raw materials and equipment used in the present invention are all known products, which are obtained by purchasing commercially available products.

[0049] 4-Vinylbenzyl chloride (VBC), azobisisobutyronitrile (AIBN), polyvinylpyrrolidone (PVP), styrene (St), branched polyethyleneimine (BPEI, average weight average molecular weight Mw = 25000), and trimethylamine (TMA, 30% ethanol solution) were all purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.

[0050] The "room temperature" referred to in the present invention is 25±5°C.

[0051] Example 1. Preparation of polymer nanosphere composite anion exchange membrane

[0052] 1. Preparation of PVBC nanospheres

[0053] Under nitrogen purging, 30mL VBC, 0.34g AIBN and 2.4g PVP were added to a mixed solution containing 150mL anhydrous ethanol and 40mL deionized water, and then stirred at 70°C for reaction. When the reaction was carried out for 6h and 12h, 50mL of the dispersion after the reaction was taken, and the lower layer of solid was removed by centrifugation. After washing and filtering 3 times with deionized water saturated with nitrogen atmosphere, vacuum drying was carried out at 60°C for 6h to obtain PVBC nanospheres of different particle sizes. The prepared nanospheres of different particle sizes were named Small PVBC Microspheres (abbreviated as SPM, obtained from the dispersion after 6h of reaction) and Big PVBC Microspheres (abbreviated as BPM, obtained from the dispersion after 12h of reaction).

[0054] 2. Preparation of PS-co-QPVBC-BPEI solution

[0055] (1) Synthesis of PS-co-PVBC: Purified St and VBC, as well as AIBN (1 wt% of the reaction monomers) were added to a 50 mL double-necked round-bottom flask equipped with a magnetic stirring bar according to a molar ratio (St: VBC = 1: 1). After being mixed evenly, the round-bottom flask was purged with a dry nitrogen atmosphere for 30 min, and then reacted at 80 ° C for 24 h. After the reaction was completed, the reactants were dissolved in toluene, and PS-co-PVBC was separated by precipitation with anhydrous ethanol, and then dissolved in toluene three times and then purified by precipitation. After that, the product was vacuum dried at 60 ° C for 6 h.

[0056] (2) Synthesis of PS-co-QPVBC: PS-co-PVBC (10 g) and trimethylamine (TMA) were dissolved in an excess of dimethyl sulfoxide (DMSO) under ultrasonic treatment (the molar ratio of VBC to TMA in PS-co-PVBC was 1:0.5). Then, the solution was stirred at 80 ° C for 5 h under dry nitrogen purge. After that, the product was vacuum dried at 60 ° C for 12 h to remove DMSO to obtain a crude powder of PS-co-QPVBC. Finally, the crude PS-co-QPVBC powder was washed three times with anhydrous ethanol and vacuum dried at 40 ° C for 12 h to obtain the product PS-co-QPVBC.

[0057] (3) PS-co-QPVBC-BPEI solution: The vacuum-dried PS-co-QPVBC powder and BPEI were dissolved in DMSO solution at a mass ratio of 3:1 and stirred at room temperature for 2 h to obtain a uniform PS-co-QPVBC-BPEI solution.

[0058] 3. Preparation of AEMs doped with PVBC nanospheres

[0059] 0.007 g of SPM was added to 47 mL of PS-co-QPVBC-BPEI solution (concentration of 1.4 g / 47 mL), and a uniform dispersion was prepared after ultrasonic dispersion at room temperature for 1 h. Then, the dispersion was vacuum defoamed and poured into a polytetrafluoroethylene (PTFE) plate, placed in an oven at 80 ° C for reaction for 24 h, and nano-microsphere-reinforced interpenetrating network AEMs were prepared. Subsequently, the AEMs were immersed in a round-bottom flask filled with excess 1-bromopropane and reacted under vacuum at room temperature for 36 h to quaternize the unreacted BPEI. After that, the completely dried AEMs were immersed in a 1M NaOH solution saturated with N2 at room temperature for 48 h (the NaOH solution was replaced every 24 h and monitored with AgNO3 and HNO3 until no white precipitate was produced to ensure that the Cl in the membrane - and Br - Completely converted to OH - ), and then rinsed repeatedly with N2-saturated deionized water until neutral to remove excess OH - Finally, the prepared AEMs were stored in deionized water for future use. The prepared AEMs were named SVSPM0.5. The preparation process of AEMs doped with nanospheres is as follows Figure 1 shown.

[0060] According to the formula in Table 1, referring to the preparation method of SVSPM0.5, the only difference is that the input amount of SPM is changed, and AEMs with different SPM contents are prepared: SVSPM1, SVSPM2, SVSPM4, and SVSPM6.

[0061] According to the formulation in Table 1, referring to the preparation method of SVSPM0.5, the only difference is that SPM is replaced by BPM and the input amount of BPM is changed to prepare AEMs with different BPM contents: SVBPM0.5, SVBPM1, SVBPM2, SVBPM4, and SVBPM6.

[0062] Table 1. Formulations of all AEMs

[0063]

[0064]

[0065] In Table 1, the concentration of the PS-co-QPVBC-BPEI solution was 1.4 g / 47 mL.

[0066] The following is the preparation method of the control sample.

[0067] Comparative Example 1: Preparation of AEM without Nanospheres

[0068] According to the formula in Table 1 and referring to the preparation method of SVSPM0.5, an AEM without nanospheres was prepared and named SV AEM. (See Table 1 for details).

[0069] The beneficial effects of the present invention are demonstrated by experimental examples below.

[0070] Experimental Example 1: Structural Characterization and Performance Testing of PVBC Nanospheres

[0071] 1. Experimental methods

[0072] (1) X-ray photoelectron spectroscopy (XPS): Thermo Scientific K-Alpha X-ray photoelectron spectrometer (Thermo, USA) was used to perform elemental analysis on SPM and BPM. The test voltage was 12 kV, the excitation source was Al Kα ray, and the spot size was 400 μm.

[0073] (2) Particle size analysis: The particle size of SPM and BPM was analyzed at room temperature using a Nano ZS90 nanoparticle size and Zeta potential analyzer (Malvern, UK).

[0074] (3) Scanning electron microscopy (SEM): A microsphere suspension of a certain concentration was prepared and cast on a 300-mesh copper grid and dried under vacuum at room temperature. The microphase separation structure was observed using a transmission electron microscope (Tecnai G2F20, Japan).

[0075] 2. Experimental results

[0076] (1) Structural characterization of PVBC nanospheres

[0077] like Figure 2 As shown in a and b, the XPS spectra of the two nanospheres show obvious C1s and Cl 2p peaks. Further calculations show that the Cl content in SPM and BPM is 5.66% and 6.10%, respectively, which is consistent with the Cl content in PVBC. Figure 2 c and d show that the average particle sizes of SPM and BPM are 515.1nm and 824.9nm respectively. The above results show that PVBC nanoparticles with different particle sizes have been successfully prepared.

[0078] Furthermore, the microscopic morphology of nano-microspheres SPM and BPM with different particle sizes was observed by SEM. Figure 3 As shown in a and b, both SPM and BPM present a relatively uniform spherical morphology, and the particle size is consistent with the above-mentioned particle size analysis results, which confirms each other, indicating that this study successfully prepared spherical SPM and BPM with different particle sizes. In addition, according to the EDS image of BPM ( Figure 3 c, d) It can be seen that the prepared nanospheres contain a large amount of uniformly distributed C and Cl elements, which further confirms the successful synthesis of PVBC nanospheres with different particle sizes.

[0079] (2) Thermal stability of PVBC nanospheres

[0080] This study took SPM as an example to investigate the thermal stability of PVBC nanospheres. Figure 4 As shown in the figure, PVBC nanospheres show three typical thermal degradation stages: the first stage is in the range of 30-150℃, and the initial mass loss of this part is attributed to the evaporation of a small amount of water in the PVBC microspheres; the second stage is in the range of 150-410℃, and the mass loss of this part can be attributed to the thermal decomposition of chloromethyl groups on the main polymer chain and side chains of PVBC in the microspheres; the third stage occurs above 410℃, mainly due to the degradation of a large number of main polymer chains in PVBC. In summary, it can be seen that the prepared PVBC nanospheres have good thermal stability and can meet the requirements of being used as a reinforcing material for the preparation of composite films.

[0081] Therefore, this study successfully synthesized PVBC nanospheres SPM and BPM with different particle sizes, whose average particle sizes were 515.1nm and 824.9nm, respectively. The nanospheres have good thermal stability and the initial thermal decomposition temperature is about 150℃, which meets the requirements for being used as a reinforcing material for the preparation of composite membranes.

[0082] Experimental Example 2: Structural Characterization of Polymer Nanosphere Composite Anion Exchange Membrane

[0083] 1. Experimental methods

[0084] (1) Transmission electron microscopy (TEM): AEMs were embedded in epoxy resin, cured, and vacuum dried. Then, slices (less than 100 nm thick) were prepared using an ultrathin slicer and placed on a 300-mesh copper grid. The microstructure was observed using a transmission electron microscope (Tecnai G2F20, Japan).

[0085] (2) Infrared spectroscopy analysis (FTIR): The FTIR spectrum of the crushed and dried samples was tested using the KBr pellet method, and data was collected on a Fourier transform infrared spectrometer (Nicolet IS-50, Thermo Fisher, USA). The test was conducted in transmission mode with a measurement range of 4000-600 cm -1 , step length is 4cm -1 .

[0086] (3) Scanning electron microscopy (SEM): Same as Experimental Example 1.

[0087] 2. Experimental results

[0088] Figure 5 The FTIR spectra of SV, SVSPM1 and SVBPM1AEMs are shown. It can be seen that the SV, SVSPM1 and SVBPM1AEMs spectra have -1 The hydrophilic NH4 + Peak at 2925cm -1 Symmetrical stretching vibration peaks of -CH2 in the main chain of PS-co-PVBC polymer matrix and PVBC nanospheres appeared near 1450 and 1495 cm -1 The characteristic peaks of the carbon-carbon double bonds on the benzene rings in the PS-co-PVBC polymer matrix and PVBC nanospheres appeared at 1020 cm -1 Stronger CN peaks than those in SV AEM appeared nearby, indicating that an obvious chemical reaction occurred between -CH2Cl in PVBC nanospheres and BPEI in the polymer matrix, indicating that PVBC nanospheres can be successfully introduced into SV AEM.

[0089] In this study, the microscopic morphology of the prepared AEMs doped with PVBC nanospheres was observed by SEM. Figure 6 As shown in d and i, the surface of the membrane doped with PVBC nanospheres is yellow and transparent, with a thickness of about 108.5 μm. The surface of the SV AEM without any nanospheres is smooth, dense and flat ( Figure 6 a). However, after adding PVBC nanospheres, the surface of SVSPMx and SVBPMyAEMs gradually becomes rougher with the increase of the amount of nanospheres added ( Figure 6 b, c, e, f). As the amount of microspheres added increases, obvious particles appear on the AEM surface. This is because some nanospheres aggregate after being added to the AEMs, causing the AEMs surface to become rough. As the number of aggregated nanospheres increases, they gradually precipitate from the membrane. In addition, the EDS images of the SVSPM6 AEM section and the SVBPM1 AEM surface ( Figure 6 g, h) It can be seen that the N element in the AEMs doped with PVBC nanospheres is evenly and densely distributed, laying a structural foundation for the preparation of AEMs with high ionic conductivity. The above results show that the preparation of AEMs by doping nanospheres is successful and feasible, and by adjusting the amount of PVBC microspheres, AEMs with a relatively smooth surface and appropriate thickness can be prepared.

[0090] Furthermore, this study selected SV, SVSPM1, SVSPM6, SVBPM1 and SVBPM6 AEMs, and observed the hydrophilic / hydrophobic phase separation structure of AEMs at the nanoscale before and after doping with PVBC nanospheres by TEM and AFM. Figure 7 As shown in the figure, all TEM and AFM images show alternating light and dark hydrophilic / hydrophobic regions, where the dark areas represent the hydrophilic areas formed in the AEMs, and the light areas represent the hydrophobic areas. In the SV AEM, since no nanospheres were added, the polymer matrix was tightly bound and the microphase separation was low. After adding an appropriate amount of nanospheres, the spatial volume effect of the microspheres and the formation of nanoclusters (dark patches in the figure) increased the microphase separation of the AEMs, thereby promoting the formation of ion transport channels to a certain extent and improving the ion conduction efficiency of the membrane. However, when the content of nanospheres is too high, PVBC microspheres will agglomerate in large numbers to form large clusters, resulting in obvious phase separation in the membrane, which may cause the ion transport channels to be blocked or form "islands", which is not conducive to the transport of ions. In addition, it can be observed that the microphase separation degree and nanocluster size in the BPM-doped membrane are larger than those in the SPM-doped membrane, which is caused by the particle size of the nanospheres. The above results show that the addition of PVBC nanospheres can play a role in regulating the degree of microphase separation in AEMs, thereby improving the size of ion transport channels, but the degree of microphase separation in AEMs is directly related to the particle size and addition amount of PVBC nanospheres. Therefore, by selecting appropriate nanospheres and addition amounts, it is expected to construct AEMs with high ion conductivity.

[0091] The above results indicate that PVBC nanospheres were successfully introduced into AEMs in this study, and the addition of SMP and BPM can increase the degree of microphase separation in AEMs. The size of ion transport channels in AEMs can be effectively regulated by changing the amount of nanospheres added.

[0092] Experimental Example 3: Performance test of polymer nanosphere composite anion exchange membrane

[0093] 1. Experimental methods

[0094] (1) Thermal stability test: The thermal stability of AEMs was evaluated by a thermal gravimetric analyzer (TGA, TA2950, ​​PE Company, USA). The test samples were vacuum dried (60°C) before testing. The test conditions were as follows: N2 atmosphere protection, heating rate of 10°C / min, and temperature range of 30-600°C.

[0095] (2) Mechanical properties test: AEMs specimens with a size of 40 mm × 10 mm were taken out from N2-saturated deionized water, and excess water was absorbed with filter paper, and then mechanical properties were tested at room temperature. The universal testing machine (Instron 5567, Instron, USA) was fixed with a fixture gauge length of 20 mm and a loading rate of 10 mm / min. The same sample was tested at least 5 times under the same conditions.

[0096] (3) Water absorption (WU) and swelling rate (SR) test: The WU and SR of AEMs were determined by the mass and length changes of completely dried AEMs (40 mm × 10 mm) before and after water absorption. After the AEMs specimens were dried to constant weight under vacuum at 80 °C, they were weighed and the length was measured. The specimens were then immersed in deionized water at different temperatures (20 °C, 40 °C, 60 °C and 80 °C) for 24 h, taken out, and the surface moisture was wiped off with filter paper before being weighed and the length was measured in time. The WU and SR of AEMs were calculated using the following formula:

[0097]

[0098] In the formula, W wet and W dry represent the mass of completely wetted and completely dry AEMs, respectively; L wet and L dry represent the lengths of completely wet and completely dry AEMs, respectively.

[0099] (4) Calculation of ion exchange capacity (IEC) and hydration number (λ): The ion exchange capacity reflects the number of exchangeable ions per unit mass of AEM and is generally determined by titration. - The membrane was immersed in 40 mL of 0.01 M hydrochloric acid (HCl) solution and stirred for 72 h to ensure that OH - Has been H + Neutralization. Subsequently, this study used phenolphthalein as an indicator and used 0.01 M NaOH solution (calibrated with potassium hydrogen phthalate) to titrate the residual HCl solution after soaking the membrane. The IEC of AEMs can be calculated by the following formula:

[0100]

[0101] Among them, m dis the mass of AEM completely dried to constant weight, V1 and V2 represent the volume of HCl solution used to soak AEM and the volume of NaOH solution used to titrate the residual HCl solution, respectively, and C0 represents the concentration of NaOH solution.

[0102] The number of water molecules (H2O) that can be absorbed by a single quaternary ammonium group in AEMs is expressed by the hydration number λ. The λ of AEMs can be calculated by the following formula:

[0103]

[0104] In the formula, WU (%) represents the water absorption rate of AEMs, IEC (meq.g -1 ) represents the ion exchange capacity of AEMs, and 18 represents the relative molecular mass of H2O.

[0105] (5) Calculation of ionic conductivity (σ): The ionic conductivity (σ) of AEMs strips (40 mm × 5 mm) was measured in deionized water at different temperatures (20°C, 40°C, 60°C and 80°C) using an electrochemical workstation (CHI650E, Shanghai Chenhua Instrument Co., Ltd.) using the AC impedance method (test frequency 10 kHz-0.1 Hz, test voltage 10 mV, across the membrane plane). Ionic conductivity (σ) (mS·cm -1 ) is calculated by the following formula:

[0106]

[0107] In the formula, l (cm) represents the distance between the two electrodes, S (cm 2 ) represents the cross-sectional area of ​​the AEM spline, and R (kΩ) represents the in-plane impedance value of the AEM spline.

[0108] (6) Preparation of membrane electrode (MEAs) and fuel cell performance test: MEA preparation: In order to test the battery performance of AEMs, the membrane electrode assembly (MEA) was prepared using the catalyst coating substrate (CCS) method. Specifically, a certain amount of Pt / C catalyst (Pt content is 40wt%) was dispersed in 10mL of isopropanol, and then an appropriate amount of membrane-forming liquid (solid content of the membrane-forming liquid is 3wt%, membrane-forming liquid / Pt / C=3 / 5 (w / w) was added and blended with it and ultrasonicated for 1h to prepare a catalyst ink. The catalyst ink was evenly sprayed onto a 2cm×2cm carbon paper (the Pt loading on the carbon paper was 0.5mg cm) using a N2-driven spray gun. -2 ) to obtain CCS. Subsequently, the AEM was sandwiched between two pieces of CCS and a small hot press (60°C, 2 MPa, hot press for 2 min) was used to prepare "sandwich" MEAs.

[0109] Fuel cell performance test: After the MEA was assembled into a single cell, the performance of the cell was tested at 60°C and 40% relative humidity using a fuel cell test station (Hephas Mini-L100, HEE Company, China). There was no back pressure during the test, and pure H2 and pure O2 were introduced into the test station at flow rates of 250 mL / min and 350 mL / min, respectively.

[0110] 2. Experimental results

[0111] (1) Thermal stability and mechanical properties of SVSPMx and SVBPMy AEMs doped with PVBC nanospheres

[0112] The thermal stability of AEMs has an important impact on the operating stability of fuel cells. Figure 8 a, b show the TGA-DTG curves of SV, SVSPM1, SVSPM6, SVBPM1 and SVBPM6 AEMs. These curves can be divided into three main stages: the first stage is the initial mass loss in the range of 30-150℃, which is attributed to the evaporation of a small amount of water in the AEMs; the second stage is the mass loss in the range of 150-300℃, which can be attributed to the thermal decomposition of the quaternary ammonium groups formed by the reaction between the polymer matrix side chains in the AEMs, the polymer matrix and the PVBC microspheres and BPEI; the third stage is the mass loss in the range of 300-500℃. In general, the initial degradation temperature of the quaternary ammonium groups in the SVSPMx and SVBPMy AEMs doped with nanospheres is around 150℃, which is higher than the upper limit of the operating temperature required by the fuel cell, showing good thermal stability sufficient to meet the requirements of fuel cell operation.

[0113] AEMs are also subject to many external forces such as tension and pressure when serving in fuel cells, so they need to have sufficient mechanical properties to ensure the safety and stable operation of the battery. Figure 8 As shown in c and d, compared with SV AEM, the tensile strength of AEMs doped with PVBC nanospheres of different particle sizes first increased and then decreased with the increase of the microsphere content in the membrane, while the elongation at break continued to decrease. In addition, at the same addition amount, the mechanical properties of AEMs doped with SPM microspheres of smaller particle size are slightly better than those of AEMs doped with BPM of larger particle size. Taking all factors into consideration, AEMs with the addition of 2% SPM (the tensile strength and elongation at break of SVSPM2AEM are 12.89MPa and 22.09%, respectively) and 1% BPM (the tensile strength and elongation at break of SVBPM1AEM are 12.31MPa and 23.03%, respectively) show good mechanical properties and can meet the relevant performance requirements of fuel cells for AEMs.

[0114] (2) Water absorption, swelling and ion exchange capacity of SVSPMx and SVBPMy AEMs doped with PVBC nanospheres

[0115] The water absorption rate (WU) and swelling rate (SR) of AEMs are important indicators of their dimensional stability. Fig. 9 As shown in the figure, the WU and SR of all AEMs increase with increasing temperature, and the WU and SR of AEMs doped with nanospheres increase with increasing microsphere content. Compared with the membrane doped with SPM, the WU and SR of the membrane doped with the same content of BPM are slightly larger. It can be seen that by doping with appropriate and appropriate amount of nanospheres, a moderate balance can be maintained between the WU and SR of AEMs, thereby ensuring that AEMs have good ionic conductivity and good dimensional stability.

[0116] Furthermore, this study measured the ion exchange capacity (IEC) and hydration number (λ) of SV, SVSPMx and SVBPMy AEMs. As can be seen from Table 2, the addition of nanospheres can improve the IEC of the membrane within a certain range, and the IEC of SVSPMx and SVBPMy AEMs first increases and then decreases with the increase in the amount of nanospheres added. Therefore, by controlling the amount of PVBC nanospheres with different particle sizes, the IEC and λ of AEMs can be adjusted, thereby ensuring the dimensional stability of AEMs under appropriate water absorption, which is crucial for practical fuel cell applications.

[0117] Table 2. IEC, WU and λ of SV, SVSPMx and SVBPMy AEMs a Test temperature: 20℃)

[0118]

[0119] (3) Ionic conductivity of SVSPMx and SVBPMy AEMs doped with PVBC nanospheres

[0120] In fuel cells, the core role of anion exchange membranes is to transport OH - , so it needs to have good ion conductivity. Fig.10 The ionic conductivity of SV, SVSPMx and SVBPMy AEMs at different temperatures is shown in Figure 2. Fig.10As can be seen from a and b, the ionic conductivity of all AEMs increases with increasing temperature. At the same temperature, the ionic conductivity of AEMs doped with PVBC nanospheres is slightly higher than that of SV AEM. However, when the content of PVBC nanospheres is further increased, the ionic conductivity of AEMs shows a downward trend. In addition, when the doping amount of microspheres is within an appropriate range, the ionic conductivity of SVBPMy AEMs is slightly higher than that of SVSPMy AEMs at the same addition amount. In general, when the contents of SPM and BPM are 2% and 1%, respectively, the prepared SVSPM2 and SVBPM1 AEMs have the best ionic conductivity (the conductivity at 80°C is 112.8 mS cm -1 and 110.5mS cm -1 ), which is a certain improvement over SV AEM (the conductivity at 80°C is 103.3 mS cm -1 ), which shows the promoting effect of doping with PVBC nanospheres on improving the ionic conductivity of AEMs.

[0121] (4) Fuel cell performance

[0122] Fuel cell performance testing is an indispensable part of verifying whether AEMs can be used in practice. This study selected SV AEMs without PVBC nanospheres, SVSPM2 and SVBPM1 AEMs with good comprehensive performance, assembled MEAs under the same conditions and tested their single cell performance (test conditions: 60℃, 40% RH, H2 as fuel, O2 as oxidant). Fig.11 As shown in the figure, the open circuit voltages of the three AEMs in the battery test are all higher than 0.9V, indicating that they have good gas barrier properties in the battery and can effectively prevent the crossover of H2 and O2, ensuring the safety of the battery. The test results show that SV AEM has a high current density of 270.80mAcm -2 When the peak power density is 150.33 mW cm -2 ; SVBPM1AEM at a current density of 301.26 mA cm -2 When the peak power density is 158.61mW cm -2 ; SVSPM2AEM at a current density of 375.13 mA cm -2 When the peak power density is 168.72mW cm -2 . Compared with SV AEM, the peak power density of AEMs doped with PVBC nanospheres is improved. Overall, the peak power density of SVBPM1AEM and SVSPM2AEM is increased by about 5.51% and 12.23% respectively compared with SV AEM, which proves that the addition of an appropriate amount of PVBC nanospheres can effectively improve the working performance of AEMs in batteries and demonstrates its application potential.

[0123] From the above experimental results, it can be seen that the AEMs prepared by selecting the appropriate PVBC particle size and addition have appropriate water absorption and swelling, and have good thermodynamic stability and mechanical properties, which can meet the use requirements of fuel cells. Compared with undoped nanospheres, adding an appropriate amount of SPM or BPM can significantly improve the electrochemical properties of AEMs, and doping with an appropriate amount of SPM or BPM can significantly improve the performance of fuel cells assembled from AEMs. Among them, SVSPM2 and SVBPM1 AEMs prepared by adding 2% SPM or 1% BPM have higher ionic conductivity, and the ionic conductivity at 80°C reaches 112.8mS cm -1 and 110.5 mS cm -1 , which are 9.20% and 6.97% higher than those of undoped SV AEMs, respectively. The peak power densities of SVBPM1 and SVSPM2 AEMs are 158.61 mW cm -2 and 168.72 mW cm -2 , which were approximately 5.51% and 12.23% higher than those of the SV AEM without nanospheres, respectively, demonstrating the advantages of the microsphere enhancement strategy in the preparation of efficient anion exchange membranes.

[0124] In summary, the present invention provides a polymer nanosphere composite anion exchange membrane and a preparation method and use thereof. The present invention prepares polymer nanospheres of different particle sizes by a water dispersion polymerization method, introduces them into a semi-interpenetrating network anion exchange membrane, and prepares a polymer nanosphere-doped anion exchange membrane. The polymer nanosphere composite anion exchange membrane obtained by this strategy has good thermal stability and mechanical properties, improves the electrochemical properties of the anion exchange membrane and the performance of the fuel cell assembled with the anion exchange membrane, and has good application prospects.

Claims

1. A composite anion exchange membrane, characterized in that: The composite anion exchange membrane is composed of polymer nano-microspheres and interpenetrating network type anion exchange membrane, wherein the mass ratio of the polymer nano-microspheres to the interpenetrating network type anion exchange membrane is 0.1-10:

100.

2. The composite anion exchange membrane according to claim 1, characterized in that The mass ratio of the polymer nano-microspheres to the interpenetrating network type anion exchange membrane is 1-2:

100.

3. The composite anion exchange membrane according to claim 1, characterized in that: The average particle size of the polymer nanospheres is 100 to 1000 nm, preferably 500 to 830 nm, and more preferably 515.1 to 824.9 nm.

4. The composite anion exchange membrane according to any one of claims 1 to 3, characterized in that: The polymer nano-microspheres are obtained by reacting a vinyl-containing halogenated aromatic hydrocarbon monomer, an initiator and a dispersant; the mass volume ratio of the vinyl-containing halogenated aromatic hydrocarbon monomer, the initiator and the dispersant is 10 mL: 0.1-0.2 g: 0.6-1 g.

5. The composite anion exchange membrane according to claim 4, characterized in that: The vinyl-containing halogenated aromatic hydrocarbon monomer is 4-vinylbenzyl chloride; the initiator is an azo initiator, preferably azobisisobutyronitrile; the dispersant is polyvinyl pyrrolidone; the mass volume ratio of the vinyl-containing halogenated aromatic hydrocarbon monomer, the initiator and the dispersant is 10mL:0.11g:0.8g.

6. The composite anion exchange membrane according to any one of claims 1 to 3, characterized in that: The interpenetrating network anion exchange membrane is prepared according to the following steps: (i) reacting a vinyl-containing aromatic hydrocarbon monomer, a vinyl-containing halogenated aromatic hydrocarbon monomer and an initiator to obtain a copolymer; (ii) reacting the copolymer with a quaternizing agent to obtain a quaternized copolymer; (iii) reacting the quaternized copolymer with a crosslinking agent to obtain an interpenetrating network type anion exchange membrane.

7. The composite anion exchange membrane according to claim 6, characterized in that: In step (i), the vinyl-containing aromatic hydrocarbon monomer is styrene, the vinyl-containing halogenated aromatic hydrocarbon monomer is 4-vinylbenzyl chloride; the initiator is an azo initiator, preferably azobisisobutyronitrile; the molar ratio of the vinyl-containing aromatic hydrocarbon monomer to the vinyl-containing halogenated aromatic hydrocarbon monomer is 1:0.5-1.5; the mass percentage of the initiator is 0.5-1.5wt%; the reaction is carried out under a nitrogen atmosphere; the reaction temperature is 70-90°C and the reaction time is 20-30 hours; In step (ii), the reaction is carried out under a nitrogen atmosphere; the quaternizing agent is trimethylamine; the molar ratio of the vinyl-containing halogenated aromatic hydrocarbon monomer to the quaternizing agent in the copolymer is 1:0.1-1; the solvent of the reaction is an organic solvent; the reaction temperature is 70-90° C. and the reaction time is 4-6 hours; In step (iii), the cross-linking agent is branched polyethyleneimine; the mass ratio of the quaternized copolymer to the cross-linking agent is 2 to 4:1; the reaction temperature is 10 to 40° C., and the reaction time is 1 to 3 hours.

8. A method for preparing the composite anion exchange membrane according to any one of claims 1 to 7, characterized in that: The method comprises the following steps: reacting the polymer nano-microspheres with the interpenetrating network type anion exchange membrane, vacuum degassing, and drying to obtain the composite anion exchange membrane.

9. The method according to claim 8, characterized in that The reaction temperature is 10-40° C. and the reaction time is 0.5-1.5 hours.

10. Use of the composite anion exchange membrane according to any one of claims 1 to 7 in the preparation of a fuel cell.

Citation Information

Patent Citations

  • Organic nano-composite anion exchange membrane and preparation method therefor and application thereof

    CN105237818A

  • Preparation method of alkaline anion-exchange membrane

    CN107020025A

  • Anion exchange membrane and method of making

    WO2023175410A1